TIPOLOGI PEMIMPIN DALAM PENDIDIKAN ISLAM - Mukhlis, Mukhlis (EDUKASI: Jurnal Pendidikan Islam, 2016)
Study of leadership in Islam, the term used is the word caliph, imam, ulil amr and al - mulk. Understanding of each term refers to a persons ability to position itself as a leader (leader) and leadership (leadership). Big and heavy duties of a leader, it is required to it a requirement that the complex and comprehensive, covering three main requirements; (1) the physical requirements, (2) mental spiritual requirements, and (3) the terms of expertise and capabilities. Characters who have demonstrated leadership and success, and this success that needs to be used as a role model is the character of the leadership of the Prophets and Messengers, namely; Siddiq, trust, fathanah and sermons. Four characters of this leadership needs to be developed along with the times and time.Studi kepemimpinan dalam Islam, istilah yang digunakan adalah kata khalifah, imam, ulil amr dan al - mulk. Pemahaman masing-masing merujuk pada kemampuan seseorang untuk memposisikan diri sebagai pemimpin (leader) dan kepemimpinan (leadership). tugas besar dan berat dari seorang pemimpin, diperlukan untuk itu persyaratan yang kompleks dan komprehensif, meliputi tiga persyaratan utama; (1) persyaratan fisik, (2) kebutuhan spiritual mental, dan (3) persyaratan keahlian dan kemampuan. Karakter yang telah menunjukkan kepemimpinan dan keberhasilan, dan keberhasilan ini yang perlu dijadikan panutan adalah karakter kepemimpinan Nabi dan Rasul, yaitu; Siddiq, kepercayaan, fathanah dan khotbah. Empat karakter kepemimpinan ini perlu dikembangkan seiring dengan perkembangan zaman dan waktu.